Pemberian fortifikasi multi-mikronutrien berpengaruh terhadap pertumbuhan balita keluarga miskin - Mursalim Mursalim; Muhammad Juffrie; Nenny Sri Mulyani (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2011)
Background: Underfives from poor communities are susceptible group that will unlikely have suffcient nutrition (micronutrient) meanwhile this micronutrient is essential for growth. Some studies show the supplementation of micronutrient has good effects to child growth. Therefore it is necessary to study the supply of fortified multi-micronutrient and its effect to growth of underfives from poor communities.Objective: To identify the supply of fortifed multi micronutrient and its effect to growth of underfves of 6-59 months from poor communities.Method: The study was a pre-experiment that used a group pre test-post test design. Subject were underfives of 6-59 months from poor communities that got fortifed multi micronutrient. The intervention of fortifed multi micronutrient supply was given once a week (1 sachet/day) within 4 months. Data of family characteristics and identity of the subject were collected at the beginning of the study. Measurement of physical weight and height/length, consumption recall, collection of data on disease infection (acute respiratory tract and diarrhea) were carried out at the beginning and end of the study.Results: The result of statistics test showed there was signifcant increase (p<0.05) in weight, height/length and nutrition status (z-score) to index of weight for height/length, height for age, and that there was signifcant descent to acute respiratory tract infection and diarrhea of underfves of 6-59 months from poor communities after the supply of fortifed micronutrient containing vitamin A, B1, B2, B3, B6, B12, folate acid, vitamin C, D3, E, Fe and zink.Conclusion: The supply of fortifed multi micronutrient could increase weight, height/length and nutrition status (z-score), index of weight for height/length and index of weight for age and decreased of acute respiratory tract infection and diarrhea disease in underfives of 6-59 months from poor communities.